PERSUASION IN THE LIGHT OF RESEARCH ON ADVERTISING MESSAGES - Nagody-Mrozowicz, Kazimierz; Ochoa Siguencia, Luis; Chęcinska-Kopiec, Agnieszka; Budziński, Łukasz (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The research presents the process of advertising message and the mechanisms of its influence on consumer decisions. The goal of the article is to present the findings to the research question: Do the methods and techniques used in tourism advertising messages have an impact on society? To give answer to our research question, the diagnostic survey method was adopted and a research tool was used in the form of a questionnaire, which in the interactive version was filled in by the participants of the most popular online forums. The questionnaire was available on several social networks and on a special generated page for this purpose from February 1 to May 31, 2016. The research shows that the very important mechanism of persuasion is the impact of the identification process with the person's respect and authority. An important role in the process of persuasion is also played by the content of the advertising message, which brings the recipients pleasant associations and entertains. The rules of influence used in advertising messages are no longer a new or emotional topic. Still, some moral doubts give rise to those of them which, through their physical characteristics, are difficult to grasp for human abilities and perceptive abilities, and therefore also in many cases foreign and unwanted.